2021
DOI: 10.1596/978-1-4648-1893-6
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Shared Prosperity 2022: Correcting Course

Abstract: Some rights reserved 1 2 3 4 25 24 23 22 This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy, completeness, or currency of the data included in this work and does not assume responsibility for any errors, omissions, or discrepancies in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…To estimate how much economic growth is needed to end extreme poverty, we first estimate the historical relationship between growth in GDP per capita and growth in consumption per capita in a random slope regression model, taking into account trends across and within countries. We use data for 168 countries from the World Bank's 2022 Poverty and Shared Prosperity Report 10 , converting income distributions to consumption distributions where needed. We find that, on average, when GDP per capita grows by 1%, consumption per capita grows by 0.7%, with variation between countries (the remainder of growth in GDP per capita is likely allocated to savings which would imply that the savings rate converges to around 30% in the long term).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate how much economic growth is needed to end extreme poverty, we first estimate the historical relationship between growth in GDP per capita and growth in consumption per capita in a random slope regression model, taking into account trends across and within countries. We use data for 168 countries from the World Bank's 2022 Poverty and Shared Prosperity Report 10 , converting income distributions to consumption distributions where needed. We find that, on average, when GDP per capita grows by 1%, consumption per capita grows by 0.7%, with variation between countries (the remainder of growth in GDP per capita is likely allocated to savings which would imply that the savings rate converges to around 30% in the long term).…”
Section: Resultsmentioning
confidence: 99%
“…Monetary welfare measures fail to capture all dimensions of well-being or deprivation. 10,32 Importantly, previous research suggested that pathways to ending deprivation and satisfying basic human needs can differ from pathways to eradicating monetary poverty and may be achieved at lower emissions intensity. 33 There are further some methodological challenges concerning the poverty estimates we rely on.…”
Section: Limitationsmentioning
confidence: 99%
“…Over the past 25 years, steady progress was occurring in poverty reduction until the Covid pandemic caused a significant setback. The global extreme poverty rate reached 9.3% in 2020, up from 8.4% in 2019 (World Bank, 2022). The world’s poorest people carried the steepest costs of the pandemic, their income losses were twice as high as the world’s richest, and global inequality rose for the first time in decades (Bundervoet et al , 2022).…”
Section: Sdg 1 No Poverty; Sdg 2 Zero Hunger; and Sdg 3 Good Health F...mentioning
confidence: 99%
“…The poorest also faced large setbacks in health and education which, if left unaddressed by policy action, will have lasting consequences for their lifetime income prospects. The recovery since 2020 has also been uneven, with rising food and energy prices, fueled in part by the war in Ukraine and by climate shocks and conflict hindering a swift recovery (World Bank, 2022). The recent crises have pushed the world further off track from the global goal of ending extreme poverty by 2030.…”
Section: Sdg 1 No Poverty; Sdg 2 Zero Hunger; and Sdg 3 Good Health F...mentioning
confidence: 99%
See 1 more Smart Citation